Nudge Me If You Can! Why Order Ethicists Should Embrace the Nudge Approach - Nikil Mukerji; Adriano Mannino (Journal of Business Ethics, 2022)
Order ethicists favour incentives as a means for making moral progress but largely ignore an alternative method, namely, nudging, which has come to prominence through the work of behavioural scientists in recent years. In this paper, we suggest that this is a mistake. Order ethicists have no reason to ignore nudging as an alternative method. Arguments they might press against it include worries about paternalism, manipulation, autonomy, and unintended bad consequences. These are, we argue, largely unfounded insofar as they involve misconceptions or affect incentives as well. In particular, we contend that only some, but not all, nudges are paternalistic, manipulative, and autonomy-reducing. The same is true of incentives. Also, both nudges and incentives can have unintended bad consequences. Therefore, order ethicists cannot endorse arguments against nudges without undermining their favourable view of incentives. In addition, there might be positive reasons to prefer nudges to incentives, for instance, when they are more freedom-preserving, more effective, cheaper, easier to implement, or less inequality-inducing than the latter.
Keywords: 300; Incentives; Manipulation; Nudging; Order ethics; Paternalism; Unintended consequences